BSCI-07 ACETYL-AMANTADINE AS A DIAGNOSTIC BIOMARKER IN PATIENTS WITH GLIOBLASTOMA. (5th August 2022) - Mann, Anmol; Safa, Nur; Martell, Emma; Luo, Wenxia; Paul, Prasanta; Abbasian, Parandoush; Ahmed, Rashid; Sitar, Daniel; Sharif, Tanveer; Lakowski, Ted; Miller, Donald; Pitz, Marshall
Abstract: AIM: Glioblastoma (GB) is the most common malignant primary brain tumor in adults, with a prognosis as poor as 12-15 months with standard treatment. Spermidine/spermine N1-acetyltransferase (SAT1) is a rate limiting enzyme in polyamine metabolism and has been reported to be upregulated in various cancers, including GB. Amantadine is a Health Canada approved drug that is acetylated by SAT1. We established a clinical trial in GB patients to determine if plasma and urine acetyl amantadine (Ac-Am) can be used to measure SAT1 activity and whether levels correlate with their tumor burden. METHODS: A clinical trial was established that is currently active and recruiting patients with GB who receive care at CancerCare Manitoba. A total of n=8 participants have been recruited thus far. Participants' blood and urine were collected two hours after ingesting amantadine (200 mg). Levels of serum and urine Ac-Am were measured using liquid chromatography-tandem mass spectrometry. Acetyl-amantadine levels were correlated with tumour bidimensional diameter and volume measured on MRI. In addition, expression of SAT1 was examined in various cultured GB cells (both cell lines and patient-derived cells) and correlated with Ac-Am. RESULTS: Preliminary results indicate that the levels of plasma Ac-Am in study participants positively correlate with their initial tumor burden (r = 0.41). While transient increases in plasma and urine Ac-Am above baseline levels were observed, the clinical significance of these findings is undergoing further analysis. SAT1 was detected in all the GB tumor cells examined. The production of Ac-Am in cultured GB cells varied as a function of SAT1 expression. SIGNIFICANCE: A diagnostic biomarker, such as Ac-Am, that could effectively and reliably detect tumor progression and recurrence would be an invaluable adjunct to MRI imaging and could significantly impact the timing of appropriate treatment and reduce patients' morbidity and mortality.